Pelatihan Pengolahan Singkong menjadi Keripik bagi Pemuda untuk Meningkatkan Kreatifitas di Masa Covid-19 di Desa Sukadana - Terasne Terasne; Tri Setianingsih; Ahmad Hanan; Sri Sukarni; Baiq Zuhrotun Nafisah (LPPM Universitas Bumigora, 2021)
This Community Service Activity (PKM) aimed to improve skill (creativity) and increase the knowledge of Sukadana village youth to be more creative in their activities even at home during the Covid-19 period and create opportunities to become new entrepreneurs based on cassava processing of the Sukadana village community for youth and surrounding communities namely teachers and students through training in processing cassava into